The Effect of High Workload and Organizational Communication on Air Traffic Controller (ATC) Work Engagement at the PERUM LPPNPI Palembang Branch with Interpersonal Conflict as an Intervening Variable - Nugroho, Wahyu Dwi; Syauta, Jack Henry; Nurhayati, Mafizatun (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study examines how workload and organizational communication impact work engagement among air traffic controllers at AirNav Indonesia, Palembang, with interpersonal conflict as an intervening variable. Using a causal quantitative design with a structural equation model, findings show that a high workload negatively affects work engagement through increased interpersonal conflict. In contrast, effective organizational communication enhances work engagement and reduces conflict. Thus, while workload diminishes engagement through conflict, good communication boosts engagement and minimizes conflicts among air traffic controllers.